INTERCULTURAL COMMUNICATION IN LEARNING AND TEACHING FOREIGN LANGUAGES - Jalilova Dildora Sheralievna (Journals Park Publishing, 2023)
This article gives the reader information about linguo-cultural teaching and learning, besides that, it provides with the ways of effective intercultural communication.
Keywords: Conceptual world, phraseology, intercultural, negotiate, ethnic groups, neighborhood communities.